(untitled) (Research, Society and Development, 2025)
This study investigates the heat-generation mechanisms in lithium-ion batteries used in electric and hybrid vehicles, analyzing their impact on performance and the solutions adopted to control temperature. Based on a literature review, the main thermal management strategies currently applied were examined, including air cooling, liquid cooling, phase-change materials, and heat pipes. The literature indicates that the optimal thermal operating range lies between 25 °C and 40 °C; temperatures above this threshold compromise cell integrity, accelerate aging processes, and significantly increase the risk of thermal runaway, considered the primary safety challenge. The reviewed studies demonstrate that geometric optimizations, material adjustments, and improvements in thermal-management system arrangements contribute to greater temperature uniformity, enhanced heat dissipation, and mitigation of thermal failures. Improving cooling systems is essential and integrating them with intelligent technologies represents a promising solution for the future of electric vehicles.